2010
DOI: 10.1590/s1516-18462010005000062
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação das habilidades auditivas em crianças com alterações de aprendizagem

Abstract: OBJETIVO: comparar o desempenho na Avaliação Simplificada do Processamento Auditivo (ASPA) e no Pediatric Speech Intelligibility Test (PSI), de crianças com alteração de Aprendizagem da Leitura e Escrita e sem este tipo de alteração. MÉTODOS: participaram da pesquisa 28 crianças na faixa etária de 8 a 12 anos, do sexo masculino e feminino. Os participantes foram submetidos ao Teste de Desempenho Escolar (TDE) para a categorização dos grupos de estudo e controle, e, para avaliação das habilidades auditivas fora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 15 publications
3
17
1
12
Order By: Relevance
“…Other studies found similar numbers of such alterations 21,22 . Therefore, those students had problems with their verbal auditory temporal ordering ability, which warrants the investigation of the integrity of auditory processing in schoolchildren.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Other studies found similar numbers of such alterations 21,22 . Therefore, those students had problems with their verbal auditory temporal ordering ability, which warrants the investigation of the integrity of auditory processing in schoolchildren.…”
Section: Resultssupporting
confidence: 59%
“…The literature also points to a relationship between learning deficits and poorer outcomes in the verbal sequential memory test 21,22 . In the teaching-learning process, children should perceive the content conveyed by the teacher's speech, which requires adequate information processing 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Extensive research, using the SSW test for evaluating AP, has been carried out on clinical populations assessing: difficulties in learning to read and write 1,4,[8][9][10][11] , the relationship between phonological disorder and AP [12][13][14][15][16][17][18] ; the relationship between oral breathing and the central auditory system 19 ; dyslexia 20 ; comorbidity between attention deficit hyperactive disorder (ADHD) and dyslexia 21 ; the relationship between performance in cognitive tests and AP tasks 22 ; listening skills in students aged 7 to 10 years, from different socioeconomic and cultural levels 23 and effectiveness of an informal program of specific auditory training for Auditory Processing Disorders (APD) in a group of 24 patients with this alteration.…”
Section: Methodsmentioning
confidence: 99%
“…This study aims to highlight the importance of SSW test in the diagnosis of human communication disorders and to identify children at risk for learning disorders and specific complications which can be overcome or minimized with concomitant auditory training and speech therapy 1,4,[8][9][10][11][12]18 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation